Safe silicon-carbon negative electrode lithium ion battery and preparation method thereof
By introducing ceramic powder and single-walled carbon nanotube coatings into the positive electrode and separator, and adding flame-retardant additives to the electrolyte, the thermal runaway problem of silicon-carbon negative electrode lithium-ion batteries has been solved, achieving a high-safety lithium-ion battery.
Patent Information
- Application Number
- CN202511252261.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-12-09
AI Technical Summary
Existing silicon-carbon anode lithium-ion batteries have poor thermal stability at high temperatures and are prone to thermal runaway, resulting in failure to pass the nail penetration test and failing to meet the high safety requirements of wearable devices.
By introducing coatings of materials such as ceramic powder and single-walled carbon nanotubes into the positive electrode and separator, and adding flame-retardant additives such as trimethyl phosphate and trimethyl borate to the electrolyte, the mechanical strength and thermal stability of the battery are enhanced, and the risk of internal short circuit is reduced.
It significantly improves the durability and safety of lithium-ion batteries, with a 100% pass rate in the needle penetration test, meeting the high safety requirements of wearable devices.
Smart Images

Figure CN121097176A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium ion batteries, in particular to a safe silicon-carbon negative electrode lithium ion battery and a preparation method thereof. BACKGROUND
[0002] With the pursuit of clean energy and sustainable development around the world, the rapid development of electric vehicles, wearable devices and large-scale energy storage systems has made increasingly stringent demands on the performance of lithium ion batteries. Among them, silicon-carbon composite material has become a new generation of negative electrode material due to its high specific capacity and excellent cycle performance. Silicon-carbon negative electrode battery is a battery in which silicon is doped in traditional negative electrode material graphite to improve the energy density of the battery. For example, the content of artificial graphite silicon in portable wearable batteries is about 6% to 10%, so as to increase the battery capacity without increasing the battery size, effectively prolonging the endurance time.
[0003] Since the silicon-carbon negative electrode is a nanomaterial, its thermal stability is relatively poor, and the internal structure and chemical properties of the silicon-carbon negative electrode material are prone to change in a high-temperature environment: the reaction activity rate of silicon and electrolyte increases significantly with increasing temperature, causing the silicon-based negative electrode to be more prone to thermal decomposition reaction and side reaction at high temperature. In addition, organic solvents such as carbonates in the electrolyte will also decompose at high temperature to generate carbon monoxide, carbon dioxide and other gases. These decomposition reactions further exacerbate the temperature rise inside the battery, ultimately leading to thermal runaway, making the safety needle test unqualified. Currently, the existing silicon-carbon negative electrode system lithium ion battery has a very violent needle trigger thermal runaway experiment under full charge, mainly in the form of relatively continuous and violent sparks, and the needle penetration rate is about 5% to 10%, which cannot meet the daily use requirements of silicon-carbon negative electrode batteries with high safety. SUMMARY
[0004] In order to overcome the shortcomings of the prior art, one of the purposes of the present application is to provide a safe silicon-carbon negative electrode lithium ion battery, which can greatly improve the puncture resistance and safety while maintaining the performance of the battery, with a needle test qualified rate of 100%, which can well meet the daily use high safety requirements of wearable silicon-carbon negative electrode batteries with a capacity of 2Ah or less.
[0005] To solve the above problems, the technical scheme adopted by the present application is as follows: A safe silicon-carbon negative electrode lithium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, the positive electrode sheet, the separator, the negative electrode sheet and the separator are sequentially stacked and then wound into a roll core, the roll core is arranged in the shell, and the electrolyte is contained in the shell and permeates the roll core. The positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating layer arranged on the surface of the positive electrode current collector, and a primer coating layer is arranged between the positive electrode current collector and the positive electrode active coating layer; the primer coating layer comprises ceramic powder, single-walled carbon nanotubes and a binder; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating layer arranged on the surface of the negative electrode current collector. The separator comprises a base film and a ceramic coating layer arranged on the surface of the base film, and an oil-based coating layer is coated on the ceramic coating layer; the oil-based coating layer is composed of aramid, PVDF and an organic solvent. The electrolyte comprises lithium salt, organic solvent and flame-retardant additive, and the flame-retardant additive is composed of trimethyl phosphate, trimethyl borate and chloroethylene carbonate.
[0006] As a preferred embodiment of the present application, the use amount of each component in the primer coating layer is: ceramic powder 75% to 85%, single-walled carbon nanotubes 2% to 10%, and binder 5% to 15%.
[0007] Further preferably, the ceramic powder is aluminum oxide or boehmite; and the binder is at least one of PMMA, PVDF and PAA.
[0008] As a preferred embodiment of the present application, the positive electrode active coating layer comprises the following components by mass percentage: PVDF 0.5% to 1.0%, NMP 0.5% to 1.0%, lithium cobaltate 96.5% to 98%, conductive carbon black 0.5% to 1.0%, and carbon nanotubes 0.5% to 1.0%.
[0009] As a preferred embodiment of the present application, the negative electrode active coating layer comprises the following components by mass percentage: sodium carboxymethyl cellulose 0.5% to 1.0%, artificial graphite 88% to 92%, silicon 6% to 10%, binder 0.5% to 1.0%, and conductive agent 0.5% to 1.0%.
[0010] As a preferred embodiment of the present application, the mass percentage use amount of each component in the oil-based coating layer is: aramid 3% to 5%, PVDF 5% to 7%, and organic solvent 88.0% to 92.0%.
[0011] As a preferred embodiment of the present application, the porosity of the base film is > 40%.
[0012] As a preferred embodiment of the present application, the mass percentage use amount of each component in the electrolyte is: lithium salt 10% to 12%, organic solvent 81% to 85%, and flame-retardant additive 4.5% to 7%; wherein the use amount of trimethyl phosphate in the flame-retardant additive is 3% to 4%, the use amount of trimethyl borate is 1% to 2%, and the use amount of chloroethylene carbonate is 0.5% to 1%.
[0013] The application also provides a preparation method of the safety type silicon-carbon negative lithium ion battery as described above, which comprises the following steps: S1, preparation of the positive electrode sheet: S11, dissolving the formula amount of ceramic powder, single-walled carbon nanotube and binder in a solvent to prepare a primer slurry; uniformly coating the primer slurry on an aluminum foil, drying and then rolling to prepare a positive electrode current collector coated with a primer coating layer; S12, uniformly mixing the formula amount of PVDF and NMP to prepare a positive electrode glue solution, adding the formula amount of lithium cobaltate, conductive carbon black and carbon nanotube, stirring to fully mix them, and then preparing a positive electrode active slurry; S13, uniformly coating the positive electrode active slurry of step S12 on the positive electrode current collector prepared in step S11, vacuum drying at 55-70°C for 6-8h, and then rolling at a pressure of 0.3-0.6MPa to prepare a positive electrode sheet with a thickness of 100-110μm and a compacted density of 4.05-4.15g / cm 3 ; S2, preparation of the negative electrode sheet: S21, dissolving the formula amount of sodium carboxymethyl cellulose in deionized water to prepare a negative electrode glue solution, adding the formula amount of artificial graphite, silicon, binder and conductive agent, stirring to fully mix them, and then preparing a negative electrode active slurry; S22, uniformly coating the negative electrode active slurry on the surface of a copper foil, vacuum drying at 55-70°C for 6-8h, and then rolling at a pressure of 0.3-0.6MPa to prepare a negative electrode sheet with a thickness of 110-140μm and a compacted density of 1.7-1.8g / cm 3 ; S3, preparation of the separator S31, adding ceramic powder into a solvent, stirring to uniformly prepare a ceramic slurry; coating the ceramic slurry on the surface of a base film subjected to corona treatment, and then vacuum drying to prepare a base film coated with a ceramic coating layer; S32, dissolving the formula amount of aramid and PVDF in a polar solvent, stirring to uniformly mix them, and then preparing an oil-based slurry; coating the oil-based slurry on the ceramic coating layer of the base film, immersing in a non-polar solvent, and then water-based and vacuum drying to prepare a separator coated with an oil-based coating layer; S4, preparation of the winding core After welding the tabs on the positive electrode sheet and the negative electrode sheet respectively, sequentially stacking and winding in the order of the positive electrode sheet, the separator, the negative electrode sheet and the separator to prepare a winding core, and then containing the winding core in an aluminum plastic film; S5, preparation and injection of the electrolyte The formula amount of lithium salt and flame retardant additive are added into an organic solvent, mixed uniformly to prepare an electrolyte; the electrolyte is injected into a roll core with an aluminum plastic film, vacuum sealed, fully rested, and pressure formed, and the lithium ion battery is charged to a full charge state under a pressure of 0.6-1.2 MPa, to obtain a silicon-carbon negative electrode lithium ion battery.
[0014] As a preferred embodiment of the present application, the solid content of the positive electrode active paste in step S12 is 74%-77%, and the viscosity is 4000-8000 mPa·s; the solid content of the negative electrode active paste in step S21 is 45%-50%, and the viscosity is 8000-12000 mPa·s.
[0015] Compared with the prior art, the present application has the following beneficial effects: The silicon-carbon negative electrode lithium ion battery of the present application can buffer and isolate external force impact by coating a primer coating layer on the positive electrode current collector aluminum foil, can cover the small defects and burrs on the surface of the aluminum foil, reduce the possibility of direct contact between the aluminum foil and the negative electrode active material, thereby reducing the risk of internal short circuit and thermal runaway, and effectively improving the safety of the battery; by coating a ceramic layer and an oil-based coating layer composed of aramid and PVDF on both sides of the base film with low closed pores and high film breaking temperature, the dense ceramic coating layer plays a protective role, can significantly improve the thermal stability and mechanical strength of the separator, and the oil-based coating layer can further improve the mechanical strength, thermal stability and electrochemical performance of the separator; the electrolyte contains a composite flame retardant additive composed of trimethyl phosphate, trimethyl borate and chloroethylene carbonate, has good thermal stability, can inhibit the decomposition of the electrolyte at high temperature, and further improves the safety of the lithium ion battery.
[0016] The lithium ion battery of the present application can greatly improve the puncture resistance and safety while maintaining the performance of the battery, and the needle test qualified rate reaches 100%, and the capacity of the battery below 2 Ah can well meet the daily use high safety demand of wearable silicon-carbon negative electrode batteries. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 The structure diagram of the separator of the present application; Figure 2 The process flow chart of the preparation method of the safety silicon-carbon negative electrode lithium ion battery of the present application; Figure 3 The comparison chart of the capacity retention rate of the room temperature cycle performance of Example 1 and Comparative Example 1 of the present application; Figure 4 The comparison chart of the thickness expansion rate of the room temperature cycle performance of Example 1 and Comparative Example 1 of the present application.
[0018] Explanation of reference numerals: 1, base film; 2, ceramic coating layer; 3, oil-based coating layer. Detailed Implementation
[0019] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0020] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0021] This invention provides a safe silicon-carbon negative electrode lithium-ion battery. The lithium-ion battery includes a positive electrode, a negative electrode, a separator, an electrolyte, and a casing. The positive electrode, separator, negative electrode, and separator are stacked in sequence and then wound into a core. The core is disposed inside the casing, and the electrolyte is contained inside the casing and permeates into the core. Positive electrode sheet The positive electrode includes a positive current collector aluminum foil with a thickness of 9µm to 12µm. The surface of the positive current collector is coated with a base coating and a positive active coating from the inside out, and the total thickness of the positive current collector and the positive coating is 11µm to 19µm.
[0022] Specifically, the primer coating comprises ceramic powder, carbon nanotube conductive agent, and binder. Coating the positive electrode current collector aluminum foil with this primer coating enhances the conductivity and oxidation resistance of the positive electrode current collector, thereby reducing the battery's internal resistance and improving its charge / discharge efficiency and rate performance. It also increases heat resistance and adhesion. In the needle penetration test of silicon-carbon batteries, when a steel needle is used as the positive electrode current collector, the primer coating provides a certain buffering and isolation effect against external forces such as needle penetration. Simultaneously, the primer coating can cover minor defects and burrs on the aluminum foil surface, reducing the possibility of direct contact between the aluminum foil and the negative electrode active material, thus reducing the risk of short circuits and improving battery safety. Preferably, the single-sided coating thickness of the primer coating is 2µm to 5µm, and the double-sided coating thickness is 4µm to 10µm.
[0023] The ceramic powder can provide high thermal stability and corrosion resistance to the primer coating. The ceramic powder includes, but is not limited to, aluminum oxide and boehmite. The carbon nanotube conductive agent is preferably single-walled carbon nanotubes. The single-walled carbon nanotubes have excellent electrical properties and better conductivity than copper. The addition of single-walled carbon nanotubes to the primer coating can effectively reduce the contact resistance between the aluminum foil and the active material, making the transmission of electrons between the aluminum foil and the active material smoother, thereby improving the charge and discharge efficiency and rate performance of the battery. The single-walled carbon nanotubes can form a three-dimensional network structure to tightly connect the aluminum foil and the active material particles together, enhancing the adhesion between the active material and the aluminum foil, reducing the shedding of the active material during the charge and discharge process, and improving the cycle life and stability of the battery. During the charge and discharge process of the battery, the surface of the aluminum foil is prone to react with the electrolyte to form an aluminum oxide film with poor conductivity, affecting the performance of the battery. The single-walled carbon nanotubes can form a protective film on the surface of the aluminum foil to prevent direct contact between the aluminum foil and the electrolyte, thereby improving the stability of the interface and prolonging the service life of the battery. At the same time, the single-walled carbon nanotubes have extremely high flexibility and strength, which can improve the flexibility of the aluminum foil, making it less prone to breakage or damage during the manufacturing and use of the battery, and improving the safety and reliability of the battery. The binder is selected from at least one of polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyacrylic acid (PAA).
[0024] The mass percentage of each component in the primer coating is as follows: ceramic powder 75% to 85%, single-walled carbon nanotubes 2% to 10%, and binder 5% to 15%. In some embodiments, the mass percentage of each component in the primer coating is as follows: ceramic powder 78% to 82%, single-walled carbon nanotubes 2% to 9%, and binder 8% to 13%. In some embodiments, the mass percentage of each component in the primer coating is as follows: ceramic powder 75% to 80%, single-walled carbon nanotubes 5% to 10%, and binder 12% to 15%. In some embodiments, the mass percentage of each component in the primer coating is as follows: ceramic powder 78% to 83%, single-walled carbon nanotubes 3% to 8%, and binder 10% to 15%.
[0025] The positive active coating is coated on the primer coating layer of the positive current collector double-sided, to improve the capacity and endurance of the battery. Specifically, the positive active coating includes the following components by mass percentage: PVDF 0.5~1.0%, NMP 0.5~1.0%, lithium cobaltate 96.5~98.5%, conductive carbon black 0.5~1.0%, carbon nanotube 0.5~1.0%. In some embodiments, the mass percentage of each component in the positive active coating is as follows: PVDF 0.5~0.8%, NMP 0.5~0.8%, lithium cobaltate 97.6~98%, conductive carbon black 0.5~0.8%, carbon nanotube 0.5~0.8%. In some embodiments, the mass percentage of each component in the positive active coating is as follows: PVDF 0.6~0.8%, NMP 0.6~0.8%, lithium cobaltate 97~97.5%, conductive carbon black 0.6~0.8%, carbon nanotube 0.6~0.8%. In some embodiments, the mass percentage of each component in the positive active coating is as follows: PVDF 0.4~0.8%, NMP 0.7~1.5%, lithium cobaltate 96.0~98.0%, conductive carbon black 0.4~0.8%, carbon nanotube 0.4~0.9%.
[0026] Negative electrode sheet The negative sheet includes a negative current collector copper foil, and the thickness of the negative current collector is 4.5um~6um. The upper and lower surfaces of the negative current collector are coated with a negative active coating. Specifically, the negative active coating includes the following components by mass percentage: thickening agent sodium carboxymethyl cellulose (CMC) 0.5%~1.0%, artificial graphite 88%~92%, silicon 6%~10%, binder 0.5%~1.0%, conductive agent 0.5%~1.0%. Preferably, the binder is a combination of binder products with model numbers LA136DL and SN-307; the conductive agent is a combination of conductive agent products with model numbers LB212C-42 and Super-p. In some embodiments, the mass percentage of each component in the negative active coating is as follows: thickening agent sodium carboxymethyl cellulose (CMC) 0.7%~0.8%, artificial graphite 89~90%, silicon 7~9%, binder 0.7~0.8%, conductive agent 0.7~0.8%. In some embodiments, the mass percentage of each component in the negative active coating is as follows: thickening agent sodium carboxymethyl cellulose (CMC) 0.6%, artificial graphite 90%, silicon 8%, binder 0.7%, conductive agent 0.7%.
[0027] Separator As Figure 1As shown, the separator includes a base film and a ceramic coating 2 arranged on both surfaces of the base film 1, and an oil-based coating 3 is coated on the ceramic coating 2. The ceramic coating can enhance the adsorption capacity of the electrolyte, reduce the fission of the separator after the needle puncture of the battery cell, increase the adhesion between the separator and the pole piece, and inhibit the expansion of the silicon-carbon negative electrode; wherein the base film is a porous high-strength PE film with a low closed pore temperature and a high film breaking temperature, and the base film can provide good mechanical support and chemical stability. The closed pore temperature refers to the temperature at which the micropores are closed, and the film breaking temperature refers to the temperature at which the separator is broken and melted. When the battery generates a large amount of heat, the temperature approaches the melting point of the polymer of the base film, the micropores are closed to form a thermal shutdown, which can block the ion transmission to form an open circuit, thereby protecting the battery and further improving the safety performance of the battery. Preferably, the porosity of the base film is >40%, the film breaking temperature is 205-230°C, and the closed pore temperature is 120-130°C.
[0028] The ceramic coating includes fillers, binders and solvents, wherein the fillers are usually selected from inorganic nanoparticles such as alumina, which has high hardness, high wear resistance and good chemical stability; the binders are used to improve the bonding strength between the fillers and the base film, ensure the firm adhesion of the ceramic coating on the surface of the separator, maintain the structural integrity of the coating and prevent the coating from falling off or being damaged during use. The ceramic coating is coated on the surface of the base film to form a dense protective layer, which can reduce the thermal shrinkage of the width of the separator at high temperature and significantly improve the thermal stability and mechanical strength of the separator. The amount ratio of the components in the ceramic coating is: fillers 30%-40%, binders 10%-20%, solvents 45%-55%. The solvent is preferably deionized water. The oil-based coating is coated on the surface of the ceramic coating, and the oil-based coating is composed of aramid and PVDF: aramid is a high-performance fiber material with the characteristics of small specific gravity, high strength, high modulus, good heat resistance and strong flame retardance, and PVDF (polyvinylidene fluoride) has good adhesion and chemical stability. The oil-based coating composed of aramid and PVDF can further improve the mechanical strength, thermal stability and electrochemical performance of the separator, can secondarily enhance the heat resistance of the separator, effectively enhance the anti-puncture function of the separator, and can make the adhesion of the separator and the pole piece more firm, effectively reduce the shell entry failure rate of the battery product, and improve the production yield and reliability of the battery. In the needle puncture test, when the steel needle penetrates the separator, the ceramic coating and the oil-based coating can effectively resist the impact force of the needle puncture and prevent the separator from being punctured or torn and damaged. By using the high strength characteristics of aramid and the adhesion of PVDF, the separator can maintain structural integrity when subjected to external impact. When a short circuit or overheating occurs inside the battery, the ceramic coating and the oil-based coating can also effectively prevent the rapid transmission and diffusion of heat, improve the thermal stability, and even if the separator has a certain size of thermal shrinkage, the thermal shrinkage of the oil-based coating is less than 5% at 180℃, which greatly reduces the thermal shrinkage rate of the separator at high temperature, so the integrity of the separator can be maintained, the direct contact between the positive and negative electrodes can be prevented to cause short circuit, and the safety of the battery can be ensured, thereby reducing the risk of battery thermal runaway. In addition, aramid is a polar organic polymer with high wettability to electrolyte, which can further improve the wettability and liquid retention capacity of the separator to electrolyte, which is beneficial to the transmission of lithium ions in the separator, thereby improving the charge and discharge efficiency, energy density and cycle life of the battery. PVDF has good liquid retention and wettability, and when the steel needle penetrates the separator, PVDF can absorb and retain more electrolyte and prevent leakage.
[0029] Preferably, the coating thickness of the oil-based coating is 1-2 μm, which can reduce the amount of material, thereby reducing production costs and improving production efficiency. The mass percentage of each component in the oil-based coating is: aramid fiber 3-5%, PVDF 5-7%, and organic solvent 88.0-92.0%. In some embodiments, the mass percentage of each component in the oil-based coating is: aramid fiber 4-6%, PVDF 4-6%, and organic solvent 88.0-92.0%. In some embodiments, the mass percentage of each component in the oil-based coating is: aramid fiber 5%, PVDF 7%, and organic solvent 88.0%.
[0030] Electrolyte The electrolyte comprises a lithium salt, an organic solvent, and a flame-retardant additive composed of trimethyl phosphate (TMP) and trimethyl borate (TMB). By adding the composite flame-retardant additive to the electrolyte, the flame retardancy of the electrolyte can be effectively improved, the heat release value and the self-heating rate of the battery can be reduced, the thermal stability of the electrolyte itself can be increased, the decomposition of the electrolyte can be simultaneously inhibited, the electrode / electrolyte interface can be effectively improved, the exothermic reaction can be inhibited, and the possibility of thermal runaway can be reduced, thereby effectively reducing the risk of fire and explosion of the battery under misuse conditions and further improving the safety performance of the battery.
[0031] Specifically, the amount of each component in the electrolyte is: lithium salt 10-12%, organic solvent 81-85%, and flame-retardant additive 4.5-7%. In some embodiments, the amount of each component in the electrolyte is: lithium salt 11-12%, organic solvent 82-84%, and flame-retardant additive 5-6%. In some embodiments, the amount of each component in the electrolyte is: lithium salt 12%, organic solvent 83%, and flame-retardant additive 5%.
[0032] The lithium salt is an inorganic lithium salt or an organic lithium salt. The inorganic lithium salt is preferably lithium hexafluorophosphate (LiPF6) or lithium tetrafluoroborate (LiBF4). Lithium hexafluorophosphate has high ionic conductivity and electrochemical stability, and has relatively optimal comprehensive performance in carbonate mixed solvent electrolyte. Lithium tetrafluoroborate has a wider working temperature range, better stability at high temperature, and better low-temperature performance. The organic lithium salt is preferably lithium bis(oxalato)borate (LiBOB) or lithium bis(fluorosulfonyl)imide (LiFSI). Both of them have high conductivity, a wide electrochemical window, and good thermal stability. Lithium bis(oxalato)borate has good film-forming performance and can directly participate in the formation of SEI film. Lithium bis(fluorosulfonyl)imide can improve the discharge capacity performance in a low-temperature environment and maintain the capacity retention rate in a high-temperature environment.
[0033] The organic solvent is a carbonate solvent, an organic ether solvent, a carboxylic acid ester solvent or a sulfite solvent. The carbonate solvent is preferably a cyclic carbonate or a chain carbonate solvent. The optional cyclic carbonate solvent is ethylene carbonate (EC) or propylene carbonate (PC), EC can be well compatible with lithium salt, and can form a stable electrolyte system, but has poor low temperature performance; PC has good low temperature performance, but the dielectric constant is slightly lower than that of EC. The optional chain carbonate solvent is dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC), DMC and DEC have good chemical stability, low viscosity and high ionic conductivity, and EMC has good solubility and ionic conductivity. The organic ether solvent is a chain ether or a cyclic ether, and the optional chain ether is dimethoxymethane (DMM) or ethylene glycol dimethyl ether (DME), DMM has high dielectric constant and good chemical stability, but has high viscosity; DME can form a stable chelate with lithium hexafluorophosphate, has strong solubility for lithium salt, and makes the electrolyte have high conductivity, but has poor chemical stability. The optional cyclic ether is tetrahydrofuran (THF) or 2-methyltetrahydrofuran, THF has high dielectric constant and good chemical stability, but has high viscosity, and 2-methyltetrahydrofuran has similar performance to THF, but has slightly better chemical stability than THF. The carboxylic acid ester solvent is ethyl acetate, methyl propionate or ethyl propionate; the sulfite solvent is dimethyl sulfite (DMS), diethyl sulfite (EMS), ethylene sulfite (ES) or propylene sulfite (PS).
[0034] The flame retardant additive is composed of trimethyl phosphate (TMP), trimethyl borate (TMB) and chlorinated ethylene carbonate, wherein trimethyl phosphate is first gasified into gaseous molecules under heat, and the gaseous molecules are decomposed to release phosphorus-containing free radicals under heat, the generated free radicals are coupled with hydrogen free radicals decomposed from the electrolyte, the content of hydrogen free radicals in the system is reduced, the combustion or explosion of hydrocarbons is prevented, the flame retardant performance of the electrolyte is improved, the heat release value and self-heating rate of the battery are reduced, the thermal stability of the electrolyte itself is increased, and the combustion or explosion of the battery under overheating conditions is avoided. Trimethyl borate is not only safe, non-toxic and odorless, but also can stabilize the thermal reaction in the battery, and significantly improve the overall safety and stability of the battery. It can combine with specific active ingredients in the electrolyte, effectively reduce the occurrence of side reactions, and at the same time promote the formation of a more stable interface film to prevent high-activity free radical chain reaction and inhibit combustion. The amount of trimethyl phosphate in the flame retardant additive is 3-4%, the amount of trimethyl borate is 1-2%, and the amount of chlorinated ethylene carbonate is 0.5%-1%.
[0035] The application also provides a preparation method of the safety type silicon-carbon negative lithium ion battery as described above, as shown in the following formula: Figure 2 The preparation method comprises the following steps: S1, preparation of positive electrode sheet: S11, dissolve or disperse the formula amount of ceramic powder, single-walled carbon nanotube and binder in solvent N-methyl pyrrolidone, filter after sufficient stirring, and prepare a uniform, particle-free and bubble-free primer slurry; uniformly coat the primer slurry on the surface of an aluminum foil with a thickness of 9-12 μm by means of a doctor blade or a slit extrusion, vacuum dry at 50-70 °C for 5-15 min, and solidify the primer slurry to form a coating layer, and roll to improve the coating density and the adhesion between the coating layer and the current collector, thereby obtaining a positive electrode current collector coated with a primer coating layer; S12, uniformly mix the formula amount of PVDF and NMP to prepare a positive electrode glue solution, add the formula amount of lithium cobaltate (LiCoO2), conductive carbon black (SP) and carbon nanotube (CNT), and stir to fully mix them, thereby obtaining a positive electrode active slurry with a solid content of 74-77% and a viscosity of 4000-8000 mPa·s; S13, uniformly coat the positive electrode active slurry of step S12 on the positive electrode current collector prepared in step S11, vacuum dry at 55-70 °C for 6-8 h, and then roll at a pressure of 0.3-0.6 MPa, thereby obtaining a positive electrode sheet with a thickness of 100-110 μm and a compacted density of 4.05-4.15 g / cm 3 ; S2, preparation of negative electrode sheet: S21, dissolve the formula amount of thickening agent sodium carboxymethyl cellulose (CMC) in deionized water to prepare a negative electrode glue solution, add the formula amount of artificial graphite, silicon, binder and conductive agent, and stir to fully mix them, thereby obtaining a negative electrode active slurry with a solid content of 45-50% and a viscosity of 8000-12000 mPa·s; S22, uniformly coat the negative electrode active slurry on the surface of a copper foil with a thickness of 4.5-6 μm, vacuum dry at 55-70 °C for 6-8 h, and then roll at a pressure of 0.3-0.6 MPa, thereby obtaining a negative electrode sheet with a thickness of 100-140 μm and a compacted density of 1.7-1.8 g / cm 3 ; S3, preparation of separator S31, add ceramic powder and binder to a solvent, uniformly stir, uniformly disperse the particles by high-speed dispersion or ball milling, filter to obtain a ceramic slurry; perform corona treatment on the low-closed-pore high-broken-membrane base film to improve the polarity of the base film; coat the ceramic slurry on both surfaces of a low-closed-pore high-broken-membrane base film with a thickness of 5-9 μm, vacuum dry at 50-70 °C for 5-15 min, and obtain a base film coated with a ceramic coating layer; S32, dissolve the formula amount of aramid and PVDF in a polar solvent, stir to mix them uniformly, and prepare an oil-based slurry; coat the oil-based slurry on the ceramic coating of the base film uniformly through a coating machine, immerse the coated separator in a non-polar solvent, and make aramid and PVDF undergo phase separation through the diffusion of the polar solvent and the non-polar solvent to form a porous structure uniformly dispersed with ceramic particles; then wash with water, and vacuum dry at 50-70℃ for 5-15 min to remove residual solvents and impurities, and prepare the separator; S4, preparation of the core After the tab is welded on the positive electrode sheet and the negative electrode sheet respectively, the positive electrode sheet, the separator, the negative electrode sheet, and the separator are sequentially stacked in order through a semi-automatic / full-automatic winding machine device to wind, and the core is prepared, and the core is accommodated in the aluminum plastic film. S5, preparation and injection of the electrolyte In an argon-filled, water-free and oxygen-free glove box, the organic solvent is subjected to dehydration and dealcoholization treatment to remove impurities and water in the organic solvent; the formula amount of lithium salt is dissolved in the treated organic solvent, heated and stirred to fully dissolve, and a lithium salt solution is formed; the flame-retardant additive is added, stirred until completely dissolved, and all components are mixed uniformly to prepare the electrolyte; the electrolyte is injected into the core with the aluminum plastic film, vacuum sealed, and fully placed at 40-50℃ for 12-20h to make the electrolyte fully infiltrate the pores of the electrode sheet and the separator, and pressurized to form, and the lithium ion battery is charged to the full charge state under the pressure of 0.6-1.2MPa to obtain the silicon-carbon negative electrode lithium ion battery.
[0036] The safety type silicon-carbon negative electrode battery prepared by the above method can effectively improve the safety performance, simultaneously maintain the functional performance of the lithium ion battery, and meet the requirements in terms of cycle number. The silicon-carbon negative electrode battery below 2.0Ah can meet the specified needle safety test by 100%, and can well meet the safety performance requirements of the digital wearable silicon-carbon negative electrode battery.
[0037] The application will be further described in detail below in combination with specific examples.
[0038] Example 1 A safety type silicon-carbon negative electrode lithium ion battery includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, and a shell, the positive electrode sheet, the separator, the negative electrode sheet, and the separator are sequentially stacked and wound into a core, the core is arranged in the shell, and the electrolyte is accommodated in the shell and absorbed in the core. In this example, the amount of each component is the amount used to prepare 1000 batteries.
[0039] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating layer arranged on the surface of the positive electrode current collector, and a primer coating layer is arranged between the positive electrode current collector and the positive electrode active coating layer. The positive electrode active coating layer comprises the following components: 0.9 kg of PVDF, 0.65 kg of NMP, 39.5 kg of lithium cobaltate, 0.95 kg of conductive carbon black, and 0.8 kg of carbon nanotubes. The primer coating layer comprises the following components: 1.2 kg of ceramic powder, 0.3 kg of single-walled carbon nanotubes 5%, and 0.65 kg of PVDF.
[0040] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating layer arranged on the surface of the negative electrode current collector; wherein the negative electrode active coating layer comprises the following components: 0.32 kg of sodium carboxymethyl cellulose, 20.5 kg of artificial graphite, 1.4 kg of silicon, 0.4 kg of a binder polyacrylic acid (PAA), and 0.6 kg of a conductive agent (single-walled carbon nanotubes).
[0041] The separator comprises a base film and a ceramic coating layer arranged on the surface of the base film, and an oil-based coating layer is coated on the ceramic coating layer; wherein the ceramic coating layer comprises the following components: 0.25 kg of aluminum oxide, 0.1 kg of a binder, and 5.45 kg of deionized water. The oil-based coating layer comprises the following components: 0.4 kg of aramid, 0.6 kg of PVDF, and 9.0 kg of acetone.
[0042] The electrolyte comprises the following components: 7.5 kg of lithium salt, 22.6 kg of organic solvent, 3.5 kg of trimethyl phosphate, 1.5 kg of trimethyl borate, and 0.6 kg of chloroethylene carbonate.
[0043] The preparation method of the safety type silicon-carbon negative electrode lithium ion battery comprises the following steps: S1, preparation of a positive electrode sheet: S11, dissolving the formula amount of ceramic powder, single-walled carbon nanotubes, and PVDF in N-methyl pyrrolidone, filtering after sufficient stirring, and preparing a uniform, particle-free, and bubble-free primer coating slurry; uniformly coating the primer coating slurry on the surface of an aluminum foil with a thickness of 10 μm by means of a doctor blade or a slit extrusion, vacuum drying at 60°C for 10 min, solidifying and shaping the primer coating slurry, and rolling to improve the coating density and the bonding force between the coating and the current collector, thereby obtaining a positive electrode current collector coated with a primer coating layer; S12, uniformly mixing the formula amount of PVDF and NMP to prepare a positive electrode glue solution, adding the formula amount of lithium cobaltate (LiCoO2), conductive carbon black (SP), and carbon nanotubes (CNT), stirring to fully mix them, and preparing a positive electrode active slurry with a solid content of 75% and a viscosity of 6000 mPa·s; S13, uniformly coating the positive active paste of step S12 on the surface of the positive current collector prepared in step S11, vacuum drying at 60℃ for 6h, and then rolling at a pressure of 0.35MPa to prepare a positive electrode sheet with a thickness of 105μm and a compacted density of 4.1g / cm 3 ; S2, preparation of a negative electrode sheet: S21, dissolving a formula amount of thickening agent sodium carboxymethyl cellulose (CMC) in deionized water to prepare a negative electrode glue solution, adding a formula amount of artificial graphite, silicon, binder and conductive agent, and stirring to fully mix them to prepare a negative active paste with a solid content of 46% and a viscosity of 9000mPa·s; S22, uniformly coating the negative active paste on the surface of a copper foil with a thickness of 5um, vacuum drying at 60℃ for 6h, and then rolling at a pressure of 0.35MPa to prepare a negative electrode sheet with a thickness of 115μm and a compacted density of 1.70g / cm 3 ; S3, preparation of a separator S31, adding ceramic powder and a binder to a solvent, stirring to prepare a ceramic slurry; coating the ceramic slurry on both surfaces of a low-closed-pore high-broken-membrane base film with a thickness of 5um, vacuum drying at 60℃ for 5min to prepare a base film coated with a ceramic coating layer; S32, dissolving a formula amount of aramid and PVDF in a polar solvent, stirring to mix them uniformly to prepare an oil-based slurry; uniformly coating the oil-based slurry on the ceramic coating layer of the base film by a coating machine, immersing the coated separator in a non-polar solvent, and allowing aramid and PVDF to undergo phase separation by the diffusion of the polar solvent and the non-polar solvent to form a porous structure uniformly dispersed with ceramic particles; then washing with water, vacuum drying at 65℃ for 10min to prepare a separator; S4, preparation of a roll core After welding tabs on the positive electrode sheet and the negative electrode sheet respectively, sequentially stacking and winding the positive electrode sheet, the separator, the negative electrode sheet and the separator in order by a full-automatic winding machine device to prepare a roll core, and containing the roll core in an aluminum plastic film; S5, preparation and injection of an electrolyte Dehydrating and dealcoholizing an organic solvent in an argon-filled, water-free and oxygen-free glove box to remove impurities and water in the organic solvent; dissolving a formula amount of lithium salt in the treated organic solvent, heating and stirring to fully dissolve the lithium salt to form a lithium salt solution; adding a flame-retardant additive, stirring until completely dissolved, and mixing all components uniformly to prepare an electrolyte; injecting the electrolyte into the roll core with the aluminum plastic film, vacuum sealing, and fully standing at a high temperature of 45℃ for 16 hours to allow the electrolyte to fully infiltrate the pores of the electrode sheet and the separator, pressurizing to 10Kg for 2.5 hours, and charging the lithium ion battery to a full charge state at a pressure of 0.4MPa to obtain a silicon-carbon negative electrode lithium ion battery.
[0044] Comparative Example 1 A silicon-carbon negative electrode lithium-ion battery includes a positive electrode, a negative electrode, a separator, an electrolyte, and a casing. The positive electrode, separator, negative electrode, and separator are sequentially stacked and wound into a core. The core is disposed inside the casing, and the electrolyte is contained inside the casing and absorbed in the core.
[0045] The difference between this comparative example and Example 1 is that: it does not contain a primer coating; the positive electrode active slurry is directly coated onto conventional high-tensile aluminum foil; a PVDF adhesive layer is coated onto the ceramic coating of the base film; and the electrolyte does not contain composite flame retardant additives. All other components and their amounts are exactly the same as in Example 1.
[0046] It is prepared according to the following method: 1. Preparation of the positive electrode: 1.1 Mix the PVDF and NMP in the specified amounts evenly to prepare a positive electrode solution. Add the specified amounts of lithium cobalt oxide (LiCoO2), conductive carbon black (SP), and carbon nanotubes (CNTs), and stir to mix them thoroughly to obtain a positive electrode active slurry with a solid content of 75.5% and a viscosity of 6000 mPa·s. 1.2 The positive electrode active slurry from step 1.1 is uniformly coated onto the surface of a positive electrode current collector made of conventional high-tensile aluminum foil. It is then vacuum dried at 60°C for 6 hours, and finally rolled under a pressure of 0.35 MPa to obtain a thickness of 102 μm and a compaction density of 4.1 g / cm³. 3 The positive electrode plate; 2. Preparation of the negative electrode: 2.1 Dissolve the thickener sodium carboxymethyl cellulose (CMC) in deionized water to prepare a negative electrode solution. Add the formulated amounts of artificial graphite, silicon, binder and conductive agent, and stir to mix them thoroughly to obtain a negative electrode active slurry with a solid content of 45.5% and a viscosity of 9000 mPa·s. 2.2 The negative electrode active slurry was uniformly coated onto the surface of a 5 μm thick copper foil, vacuum dried at 60°C for 6 hours, and then rolled with a pressure of 0.35 MPa to obtain a thickness of 110 μm and a compaction density of 1.70 g / cm³. 3 The negative electrode plate; 3. Preparation of the diaphragm The diaphragm base membrane is a conventional diaphragm, with a ceramic coating and a PVDF adhesive layer sequentially coated on the surface of the base membrane; 4. Preparation of the core After welding tabs onto the positive and negative electrode plates respectively, the positive electrode plate, separator, negative electrode plate, and separator are stacked and wound in sequence to obtain the core, which is then contained in an aluminum-plastic film. 5. Preparation and injection of electrolyte The organic solvent is dehydrated and dealcohated in an argon-filled, water-free and oxygen-free glove box to remove impurities and moisture in the organic solvent; a formula amount of lithium salt is dissolved in the treated organic solvent, heated and stirred to fully dissolve, to prepare an electrolyte; the electrolyte is injected into a roll core with an aluminum plastic film, vacuum sealed, and fully high-temperature 45℃ for 16 hours, so that the electrolyte fully infiltrates the pores of the electrode sheet and the separator, and is charged to a full charge state at a pressure of 0.4 MPa for 2.5 hours, to obtain a silicon-carbon negative electrode lithium ion battery.
[0047] I. Battery normal temperature cycle performance test 1. Capacity retention rate test method: At normal temperature 25±3℃, charge to 4.35V with 1.0C constant current, then constant voltage 4.35V until the charge cutoff current is less than or equal to 0.02C, then discharge to 3.0V with 1.0C current; repeat the above steps 500 times.
[0048] 2. Thickness expansion rate test method: Measure the thickness of the full battery in the first week of cycling and the full battery after 500 weeks of cycling, respectively, and calculate the thickness expansion rate according to the following formula: Thickness expansion rate = { (thickness after 500 weeks - thickness in the first week) / thickness in the first week} x 100%.
[0049] 3. Acceptance requirements: capacity after 500 weeks of cycling / initial capacity in the first week, capacity retention rate ≥ 80%, 500-week thickness expansion rate requirement ≤ 12%.
[0050] The results are shown in Table 1 and Figures 3~4 .
[0051] Table 1. Normal temperature cycle performance capacity retention rate and thickness expansion rate test results of the batteries prepared in Example 1 and Comparative Example 1
[0052] As can be seen from Table 1 and Figures 3~4 , the remaining capacity retention rate of the batteries prepared in Example 1 and Comparative Example 1 is high after 500 weeks of normal temperature cycling, and the thickness expansion rate of the battery normal temperature cycle test is low, both of which can meet the requirements of industry standards, indicating that the battery has high stability and safety in use.
[0053] Comparative Example 2 The difference between this comparative example and Example 1 is only that the primer coating layer comprises the following components by mass percentage: ceramic powder 85%, PVDF 15%. Other operations and parameters are exactly the same as in Example 1.
[0054] II. Battery normal temperature cycle performance test The battery prepared in Comparative Example 2 was subjected to the normal-temperature cycle capacity retention rate test according to the aforementioned method, and was compared with Example 1. The results are shown in Table 2.
[0055] Table 2 Test results of the normal-temperature cycle performance capacity retention rate of the batteries prepared in Example 1 and Comparative Example 2
[0056] As can be seen from Table 2, compared with Comparative Example 2, the single-walled carbon nanotubes added in the primer coating layer of Example 1 can improve the normal-temperature cycle performance capacity retention rate. This is because the single-walled carbon nanotubes have extremely high conductivity, can form a three-dimensional conductive network at a very low addition amount, effectively reduce the internal resistance of the battery, and improve the electron transmission efficiency. This helps to improve the charge-discharge performance and power density of the battery, and reduces the energy loss during the cycle process; the single-walled carbon nanotubes have good contact with the aluminum foil and the active material, and can form a stable conductive channel. During the charge-discharge process, even if the active material expands or shrinks in volume, the single-walled carbon nanotubes can maintain good electrical contact and avoid capacity decay caused by interface separation, which greatly improves the cycle performance capacity retention rate of the battery.
[0057] III. Different rate discharge performance capacity retention rate test The batteries prepared in Example 1 and Comparative Example 2 were subjected to different rate discharge performance capacity retention rate test, and the test method was as follows: At normal temperature 25±3℃, 0.5C constant current charging to 4.35V, then constant voltage 4.35V charging until the charging cutoff current≤0.02C, after stopping charging, standing for 0.5h~1h, discharging to the terminal voltage (3 cycles, with the highest discharge capacity as the standard) at 25℃±3℃ environment with 0.2C, 0.5C, 1.0C, 1.5C constant current, respectively.
[0058] The results are shown in Table 3.
[0059] Table 3 Test results of the different rate discharge performance capacity retention rate of the batteries prepared in Example 1 and Comparative Example 2
[0060] As can be seen from Table 3, compared with Comparative Example 2, the single-walled carbon nanotubes added in the primer coating layer of Example 1 have excellent conductivity, and the single-walled carbon nanotubes can form an efficient conductive network, significantly reduce the internal resistance of the battery, improve the electron transmission efficiency, enhance the adhesion of the coating layer to the aluminum foil substrate, reduce the interface resistance, and improve the utilization rate of the electrode material. This helps to reduce the energy loss during the charge transfer process, makes the battery output current more smoothly during high-rate discharge, improves the rate performance, and further improves the energy density and charge-discharge efficiency of the battery, and has more advantages in different rate discharge capacity retention rate.
[0061] Comparative Example 3 The difference between this comparative example and Example 1 is only that the mass ratio between aramid and PVDF in the oil-based coating is 2:8. Other operations and parameters are exactly the same as Example 1.
[0062] Comparative Example 4 The difference between this comparative example and Example 1 is only that the mass ratio between aramid and PVDF in the oil-based coating is 3:7. Other operations and parameters are exactly the same as Example 1.
[0063] Comparative Example 5 The difference between this comparative example and Example 1 is only that the electrolyte includes the following components by mass percentage: lithium salt 12%, organic solvent 88%. Other operations and parameters are exactly the same as Example 1.
[0064] Comparative Example 6 The difference between this comparative example and Example 1 is only that the electrolyte includes the following components by mass percentage: lithium salt 12%, organic solvent 85%, trimethyl phosphate 3%. Other operations and parameters are exactly the same as Example 1.
[0065] Comparative Example 7 The difference between this comparative example and Example 1 is only that the electrolyte includes the following components by mass percentage: lithium salt 12%, organic solvent 87%, trimethyl borate 1%. Other operations and parameters are exactly the same as Example 1.
[0066] Comparative Example 8 The difference between this comparative example and Example 1 is only that the electrolyte includes the following components by mass percentage: lithium salt 12%, organic solvent 85%, trimethyl phosphate 1.5%, trimethyl borate 1%, chloroethylene carbonate 0.5%. Other operations and parameters are exactly the same as Example 1.
[0067] Comparative Example 9 The difference between this comparative example and Example 1 is only that the electrolyte includes the following components by mass percentage: lithium salt 12%, organic solvent 85.5%, trimethyl phosphate 3%, trimethyl borate 0.5%. Other operations and parameters are exactly the same as Example 1.
[0068] IV. Comparison of safety performance of needle puncture 1. Test method The batteries prepared in Example 1 and Comparative Examples 1, 3-9 were respectively charged at room temperature, low temperature (-5℃) at a current of 0.5C; then a steel nail with a diameter of 2.5mm-3.5mm was vertically pierced through the center of the fully charged battery at a speed of 2m / min, and maintained for more than 60min.
[0069] 2. Instrument: battery needle puncture tester.
[0070] 3. Acceptance requirement: the battery cell does not catch fire and does not explode within the initial 60 minutes of the puncture test.
[0071] The test results are shown in Table 4.
[0072] Table 4. Needle puncture safety test results of the batteries prepared in Example 1 and Comparative Examples 1, 3-8
[0073] As shown in Table 4, the needle puncture test pass rate of the batteries prepared in Example 1 is 100%, indicating that the batteries have high puncture resistance and safety performance.
[0074] Example 2 A safe silicon-carbon negative electrode lithium ion battery, the difference between the present embodiment and Example 1 is that the amount of aramid, PVDF and organic solvent in the oil-based coating is: 0.5 kg aramid, 0.5 kg PVDF, 9.0 kg acetone, and other operations and parameters are exactly the same as Example 1.
[0075] The batteries prepared in Example 2 were subjected to needle puncture safety performance test, and the results are shown in Table 5.
[0076] Table 5. Needle puncture safety test results of the batteries prepared in Example 2
[0077] As shown in Table 5, the needle puncture test pass rate of the batteries prepared in Example 2 is high, indicating that the batteries have high safety performance and can be mass-produced, which is suitable for industrialization.
[0078] The above embodiments are only preferred embodiments of the present application, and cannot be used to limit the scope of protection of the present application. Any non-substantial changes and substitutions made by those skilled in the art based on the present application are within the scope of protection of the present application.
Claims
1. A safe silicon-carbon negative electrode lithium-ion battery, characterized in that: The device includes a positive electrode, a negative electrode, a separator, an electrolyte, and a housing. The positive electrode, the separator, the negative electrode, and the separator are sequentially stacked and wound into a core. The core is disposed inside the housing, and the electrolyte is contained inside the housing and permeates into the core. The positive electrode sheet includes a positive current collector and a positive active coating disposed on the surface of the positive current collector, with a primer coating disposed between the positive current collector and the positive active coating; the primer coating includes ceramic powder, single-walled carbon nanotubes and a binder; The negative electrode sheet includes a negative electrode current collector and a negative electrode active coating disposed on the surface of the negative electrode current collector; The diaphragm includes a base membrane and a ceramic coating disposed on the surface of the base membrane, wherein an oil-based coating is coated on the ceramic coating; the oil-based coating is composed of aramid, PVDF and organic solvent; The electrolyte comprises lithium salt, organic solvent and flame retardant additive, wherein the flame retardant additive is composed of trimethyl phosphate, trimethyl borate and chloroethylene carbonate.
2. The safe silicon-carbon negative electrode lithium-ion battery according to claim 1, characterized in that: The amounts of each component in the primer coating are: 75%~85% ceramic powder, 2%~10% single-walled carbon nanotubes, and 5%~15% binder.
3. The safe silicon-carbon negative electrode lithium-ion battery according to claim 1 or 2, characterized in that: The ceramic powder is aluminum oxide or boehmite; the binder is at least one of PMMA, PVDF, and PAA.
4. The safety silicon-carbon anode lithium-ion battery according to claim 1, characterized in that: The positive electrode active coating comprises the following components by mass percentage: PVDF 0.5%~1.0%, NMP 0.5%~1.0%, lithium cobalt oxide 96.5%~98%, conductive carbon black 0.5%~1.0%, and carbon nanotubes 0.5%~1.0%.
5. The safety silicon-carbon anode lithium-ion battery according to claim 1, characterized in that: The negative electrode active coating comprises the following components by mass percentage: sodium carboxymethyl cellulose 0.5%~1.0%, artificial graphite 88%~92%, silicon 6%~10%, binder 0.5%~1.0%, and conductive agent 0.5%~1.0%.
6. The safe silicon-carbon negative electrode lithium-ion battery according to claim 1, characterized in that: The mass percentage of each component in the oil-based coating is as follows: aramid 3%~5%, PVDF 5%~7%, and organic solvent 88.0%~92.0%.
7. The safe silicon-carbon negative electrode lithium-ion battery according to claim 1, characterized in that: The porosity of the base membrane is >40%.
8. The safe silicon-carbon negative electrode lithium-ion battery according to claim 1, characterized in that: The mass percentage of each component in the electrolyte is as follows: lithium salt 10%~12%, organic solvent 81%~85%, flame retardant additive 4.5%~7%; wherein, the amount of trimethyl phosphate in the flame retardant additive is 3%~4%, the amount of trimethyl borate is 1%~2%, and the amount of chloroethylene carbonate is 0.5%~1%.
9. A method for preparing a safe silicon-carbon negative electrode lithium-ion battery as described in any one of claims 1 to 8, characterized in that: Includes the following steps: S1. Preparation of the positive electrode: S11. Dissolve the ceramic powder, single-walled carbon nanotubes and binder in a solvent to prepare a base coating slurry; uniformly coat the base coating slurry onto an aluminum foil, dry it and roll it to obtain a positive electrode current collector coated with a base coating layer; S12. Mix the PVDF and NMP in the formula amount evenly to make a positive electrode solution. Add the lithium cobalt oxide, conductive carbon black and carbon nanotubes in the formula amount, stir to mix them thoroughly, and obtain the positive electrode active slurry. S13. The positive electrode active slurry from step S12 is uniformly coated onto the surface of the positive electrode current collector obtained in step S11. It is then vacuum dried at 55-70℃ for 6-8 hours, and finally rolled under a pressure of 0.3-0.6 MPa to obtain a thickness of 100-110 μm and a compaction density of 4.05-4.15 g / cm³. 3 The positive electrode plate; S2, Preparation of the negative electrode: S21. Dissolve the prescribed amount of sodium carboxymethyl cellulose in deionized water to prepare a negative electrode solution. Add the prescribed amounts of artificial graphite, silicon, binder and conductive agent, and stir to mix them thoroughly to obtain a negative electrode active slurry. S22. The negative electrode active slurry is uniformly coated on the surface of copper foil and vacuum dried at 55~70℃ for 6~8 hours. Then, it is rolled with a pressure of 0.3~0.6MPa to obtain a thickness of 110~140μm and a compaction density of 1.7~1.8g / cm³. 3 The negative electrode plate; S3. Preparation of the diaphragm S31. Add ceramic powder to a solvent and stir evenly to obtain a ceramic slurry; coat the ceramic slurry onto the surface of a base film that has been corona-treated, and dry it under vacuum to obtain a base film coated with a ceramic coating. S32. Dissolve the formulated amount of aramid and PVDF in a polar solvent, stir to mix them evenly, and prepare an oil-based slurry; coat the oil-based slurry onto the ceramic coating of the base film, immerse it in a non-polar solvent, and dry it in water and under vacuum to obtain a diaphragm coated with an oil-based coating. S4. Preparation of the core After welding tabs onto the positive and negative electrode plates respectively, the positive electrode plate, separator, negative electrode plate, and separator are stacked and wound in sequence to obtain the core, which is then contained in an aluminum-plastic film. S5. Preparation and injection of electrolyte The prescribed amount of lithium salt and flame retardant additives are added to an organic solvent and mixed evenly to obtain an electrolyte. The electrolyte is injected into a core with an aluminum-plastic film, vacuum sealed, and allowed to stand for a while. It is then pressurized and formed. The lithium-ion battery is charged to full charge under a pressure of 0.6~1.2MPa to obtain a silicon-carbon negative electrode lithium-ion battery.
10. The method for preparing a safe silicon-carbon negative electrode lithium-ion battery according to claim 9, characterized in that: The solid content of the positive electrode active slurry in step S12 is 74%~77% and the viscosity is 4000~8000 mPa·s; the solid content of the negative electrode active slurry in step S21 is 45%~50% and the viscosity is 8000~12000 mPa·s.
Citation Information
Patent Citations
Flame-retardant additive, co-solvent and lithium ion battery
CN107994231A
Preparation method and application of non-woven fabric coated diaphragm
CN111584797A
Manufacturing method of high-safety lithium ion battery
CN119447503A
Positive pole piece, electrochemical device and electronic device
CN119833560A
Positive plate, preparation method and application thereof, and lithium ion battery
CN119965280A